Major Kuroko-Type Deposit In The Central Izu-Ogasawara (Bonin) Arc, Japan - Kokichi Iizasa (International Marine Minerals Society, 2005)
Two major Kuroko-type deposits and minor sulfide deposits have been found in the middle Izu-Ogasawara (Bonin) Arc, Japan (Fig. 1). The Hakurei deposit, one of the major Kuroko-type deposits, was recently found in Bayonnaise knoll caldera in the nascent rift zone, which lies 20 km westward of the Sunrise deposit in Myojin knoll caldera on the Izu-Ogasawara volcanic front. The Hakurei deposit is a huge hydrothermal field measuring 500 m by 700 m in plan view. The Bayonnaise knoll caldera is mainly composed of dacite lavas and fragmental material on the caldera wall and rim, and its floor contains sediment composed of pumice, volcanic fragments, and hydrothermal clay. It is associated with a post-caldera dome and has a slightly ellipsoidal caldera rim that measures 3 km by 2.5 km, with about 200 m relief. The water depths of the caldera floor range from about 840 m to 920 m. The Kuroko-type deposit in the Bayonnaise knoll caldera occurs on the southeastern caldera floor where the caldera boundary faults intersect with a N-S-trending normal fault of the rift zone. In the deposit, many sulfide chimneys are generally less than 10 m high, and sulfide mounds are distributed around the caldera floor and on the sloping talus at the foot of the caldera wall. The deposit is buried in part by talus composed of pumice and volcanic fragments. Sulfide chimneys are still active, and inactive ones and their fragments are partly oxidized to reddish material. Chimney sulfides are mainly composed of sphalerite associated with chalcopyrite, galena, pyrite, and barite, and chemically enriched in Au up to 14 ppm and Ag up to 1400 ppm with major Zn, moderate Ba, and minor Pb, Hg, Cu, and Fe.